Răspuns :
5x-12=3x-10+[tex] x^{2} [/tex] - 2/2
5x-12=3x-10+[tex] x^{2} [/tex] - 1
-[tex] x^{2} [/tex] +5x-3x -12 + 10+1 = 0
-[tex] x^{2} [/tex] + 2x -1 = 0
Δ= b² - 4ac
Δ= 4-4
Δ= 0
[tex] x_{1,2} [/tex] = [tex] \frac{-b}{2a} [/tex]
[tex] \frac{-2}{-2} =\ \textgreater \ x_{1,2} = 1[/tex]
5x-12=3x-10+[tex] x^{2} [/tex] - 1
-[tex] x^{2} [/tex] +5x-3x -12 + 10+1 = 0
-[tex] x^{2} [/tex] + 2x -1 = 0
Δ= b² - 4ac
Δ= 4-4
Δ= 0
[tex] x_{1,2} [/tex] = [tex] \frac{-b}{2a} [/tex]
[tex] \frac{-2}{-2} =\ \textgreater \ x_{1,2} = 1[/tex]